USM-UOR TO EMBARK ON ACADEMIC AND RESEARCH COLLABORATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 21 July 2016 " Universiti Sains Malaysia (USM) and University of Ruhuna (UOR) Sri Lanka today would explore collaborative opportunities in higher education and research at the international level."